Improving workplace safety by thinking about what might have been: A first look at the role of counterfactual thinking. (February 2020) - He, Yimin; Payne, Stephanie C.; Yao, Xiang; Smallman, Rachel
Highlights: Upward counterfactual thinking (CFT) was positively related to safety behavior. Safety knowledge mediated the upward CFT-safety behavior relationships. Locus of control strengthened the mediations of safety knowledge on such relationships. Upward CFT has a stronger relationship with safety behavior than downward CFT. Abstract: Introduction: Information processing theories of workplace safety suggest that cognition is an antecedent of safety behavior. However, little research has directly tested cognitive factors as predictors of workplace safety within organizational psychology and behavior research. Counterfactuals (cognitions about "what might have been") can be functional when they consist of characteristics (e.g., "upward' – focusing on better outcomes) that alter behavior in a manner consistent with those outcomes. This field study aimed to examine the influence of counterfactual thinking on safety behavior and explanatory mechanisms and boundary conditions of that relationship. Method: A sample of 240 medical providers from a hospital in China responded to three surveys over a four-month time frame. Results: Results showed that upward counterfactuals were positively related to supervisor ratings of safety compliance and participation. These relationships were mediated by safety knowledge but not by safety motivation. Upward counterfactuals were more strongly related to safety behavior and knowledge than downward counterfactuals. As expected, safety locus of control strengthened the mediating effects of safety knowledge on the relationship between upward counterfactuals and safety behavior. Conclusions and Practical Applications: The findings demonstrated that counterfactual thinking is positively associated with safety behavior and knowledge, thus expanding the variables related to workplace safety and laying some initial groundwork for new safety interventions incorporating counterfactual thinking.